ANALISIS KEPRIBADIAN TOKOH DALAM CERPEN RUANG NEGATIF KARYA M. Z. BILLAL: PENDEKATAN PSIKOLOGI SASTRA SIGMUND FREUD - Ajeng Ismaya; Nur'anisa Rahayu; Alin Ambarwati (Jurnal PENEROKA, 2026)
This study aims to reveal the personalities of the characters in the short story Ruang Negatif by M. Z. Billal by examining how the id, ego, and superego interact to shape the actions and inner conflicts of Jamil and Ibu. Indonesian literary works, including short stories, often address psychological themes, such as trauma, loss, and parent-child relationships, as a means of emotional reflection. The focus of the study is limited to the short story text and two central characters without reviewing broader social aspects. The study uses a qualitative descriptive method with a Sigmund Freudian literary psychology approach through the process of collecting and grouping quotations related to personality structure. The analyzed data are in the form of text fragments describing the characters' behavior, feelings, and thoughts, which are then interpreted using Freud's psychodynamic framework. The research findings indicate that Jamil is able to balance the functions of the id, ego, and superego, while Ibu tends to be dominated by the superego but is still influenced by trauma from loss, which gives rise to id impulses in the form of fear. The study also found interesting things in the use of symbols in routines, such as tidying up, which reflects efforts to organize life, as well as the use of a mixed plot and an I-point of view that deepens the psychological depiction of the characters.